Bio and non-bio materials-based quasi-solid state electrolytes in DSSC: A review - Mahalingam S.; Nugroho A.; Floresyona D.; Lau K.S.; Manap A.; Chia C.H.; Afandi N. (John Wiley and Sons Ltd, 2023)
Aerogels; Dye-sensitized solar cells; Silicon solar cells; Solid electrolytes; Bio and non-bio material; Bio-materials; Cell-be; Cell/B.E; Cell/BE; Dye sensitized solar cell module; Dye- sensitized solar cells; Light intensity; Material-based; Quasi-solid state electrolytes; Hydrogels